Father and Son in the Embrace of Uncle Sam - Ileto, Reynaldo C.; (Archīum Ateneo, 2014)
This essay offers a reflection on the American sojourns of two Filipinos, Reynaldo Ileto and his father, Rafael Ileto, at two different historical periods. It brings to the fore the interplay of personal experiences and regimes of knowledge that constitute one’s belonging and response to the US empire. Rafael Ileto’s beliefs and actions are framed in light of his upbringing and his times, resulting in a military career that exemplified the special relationship between the United States and the Philippines. But the historical moment of Reynaldo Ileto’s graduate studies at Cornell University led to a path that diverged ideologically from that of his father.Keywords: US empire • Philippines • nationalism • historiography • autobiography